Characterization of phenotypic spectrum of fetal heterotaxy syndrome by combining ultrasound and magnetic resonance imaging. (1st December 2021) - Seidl‐Mlczoch, E.; Kasprian, G.; Ba‐ssalamah, A.; Stuempflen, M.; Kitzmueller, E.; Muin, D. A.; Zimpfer, D.; Prayer, D.; Michel‐behnke, I.; Ulm, B.
ABSTRACT: Objective: Heterotaxy or isomerism of the atrial appendages is a congenital disorder with variable presentation, associated with both cardiac and non‐cardiac anomalies, which may have a serious impact on fetal outcome. The aim of this exploratory study was to assess the value of fetal magnetic resonance imaging (MRI), as a complementary tool to ultrasound, for describing the morphological spectrum encountered in heterotaxy. Methods: This retrospective study included 27 fetuses that underwent fetal MRI following prenatal suspicion of heterotaxy on ultrasound from 1998 to 2019 in a tertiary referral center. Heterotaxy was classified as left atrial isomerism (LAI) or right atrial isomerism (RAI) based on fetal echocardiography (FE) examination. In addition to routine prenatal ultrasound, fetal MRI was offered routinely to enhance the diagnosis of non‐cardiac anomalies, which might have been missed on ultrasound. Prenatal findings on ultrasound, FE and MRI were reviewed systematically and compared with those of postnatal imaging and autopsy reports. Results: Twenty‐seven fetuses with heterotaxy and cardiovascular pathology, of which 19 (70%) had LAI and eight (30%) had RAI, were included. Seven (7/19 (37%)) fetuses with LAI had normal intracardiac anatomy, whereas all fetuses with RAI had a cardiac malformation. All 27 fetuses had non‐cardiac anomalies on fetal MRI, including situs and splenic anomalies. In 12/19 (63%) fetuses with LAI, a specific abnormal configuration of the liver was observed on MRI. In three fetuses, fetal MRI revealed signs of total anomalous pulmonary venous connection obstruction. An abnormal bronchial tree pattern was suspected on prenatal MRI in 6/19 (32%) fetuses with LAI and 3/8 (38%) fetuses with RAI. Conclusions: Visualization on MRI of non‐cardiac anomalies in fetuses with suspected heterotaxy is feasible and can assist the complex diagnosis of this condition, despite its limitations. This modality potentially enables differentiation of less severe cases from more complex ones, which may have a poorer prognosis. Fetal MRI can assist in prenatal counseling and planning postnatal management. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.